Synthesis, crystallographic characterization, and mechanical behavior of alumina chromia alloys. Issue 17 (1st September 2021) - Rondinella, Alfredo; Furlani, Erika; Magnan, Michele; Scagnetto, Fabio; Driussi, Stefano; Marin, Elia; Maschio, Stefano
Abstract: Powder mixtures of Alumina and Chromia, blended in different proportions (1, 3, 5 and 10%wt) by attrition milling, were fired either by pressureless sintering in air and hot pressing under vacuum. The resulting materials, characterized by X-ray diffraction, Raman spectroscopy, SEM, hardness and fracture toughness showed that all the compositions form complete solid solution which maintain the same crystal structures of corundum; chromia addition retards materials' densification of pressureless fired samples but not that of hot-pressed samples. Data from Raman spectroscopy and SEM/EDXS showed the appearance of Ti- and Mn-based impurities near the indentation print, in particular on fractured grains. The addition of chromia improves hardness, but does not affect toughness which is, on the other hand, greatly influenced by materials' residual porosity.